Gamifying Questions by Adding Context in the Creative Development Marketing Research - Michał Ścibor-Rylski (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Gamification is defined as using game design elements in non-gaming contexts: education, management, marketing and also market research. Gamifi ed research tools help to increase respondents’ engagement and obtain more in-depth results. Up till now the eff ects of gamifi cations were tested in the domains of brand strategy and consumer experience. The article shows the results of the experiment proving the eff ectiveness of a gamifi ed approach to the qualitative advertisement testing. The experimental group with a narrative context added to a question regarding the fi rst impression performed better than the control group with a standard task. Also gender differences were observed: the eff ect was valid only for men – there were no significant differences in the performance of women in both groups. Due to an uneven split of men and women and a small sample in general, this effect needs further examination